2018
DOI: 10.1186/s40723-018-0056-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of home and school on children’s happiness: a structural equation model

Abstract: Happiness is often used as a term of subjective well-being in psychology (Lyubomirsky et al. 2005a; Sagiv et al. 2004; Sheldon and Lyubomirsky 2004). If thought of in another way, happiness is an emotion combined with other positive emotions, resulting in subjective well-being when the positive emotions of a person are much more than his negative emotions, and his life satisfaction is high (Diener 2000). It is widely believed that happiness has an important and essential role in the well-being and motivation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 42 publications
8
17
0
1
Order By: Relevance
“…Our findings support, to some extent, what has been identified in previous studies [3,30,[35][36][37]; engaging in loose parts play and mindfulness can have a positive impact on playfulness and children's happiness. The absence of significant change on the physical variables such as step count and body mass index in the current study might be attributable to the short intervention period.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings support, to some extent, what has been identified in previous studies [3,30,[35][36][37]; engaging in loose parts play and mindfulness can have a positive impact on playfulness and children's happiness. The absence of significant change on the physical variables such as step count and body mass index in the current study might be attributable to the short intervention period.…”
Section: Discussionsupporting
confidence: 92%
“…It is difficult to tease out the driver for this change as it could be linked to both playfulness and mindfulness. Badri et al [37] conducted a study to investigate the structural relationship such as school and home environments on school children's happiness. The findings showed that both school and home variables directly influence the school children's happiness scores [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, family is the most fundamental factor among them and affects the others as well. In this sense, the positive effect of the family will allow children to make better decisions in terms of school, friends, and career processes and increase their happiness [ 75 , 76 , 77 , 78 , 79 ].…”
Section: Introductionmentioning
confidence: 99%
“…Solidarity and other positive 'human values' are connected with the 'traditional' way of living among Kadazandusuns (Asgard, 2004). Many studies point to the educational system (students, teachers, parents, school principals, and support staff) as being the most influential in making schools hostile or non-hostile environments (Badri et al, 2018). All the abovementioned factors explain the reasons for the effects of students' psychological well-being on their academic achievement.…”
Section: Limits and Discussionmentioning
confidence: 99%